Antifungal activities of the rhizome extract of five member Zingiberaceae against Candida albicans and Trichophyton rubrum - Muhammad Evy Prastiyanto; NI’MATUR ROHMAH; LESITA EFENDI; RAHMATIA ARIFIN; FANDHI ADI WARDOYO; WILDIANI WILSON; ANA HIDAYATI MUKAROMAH; SRI SINTO DEWI; SRI DARMAWATI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prastiyanto ME, Rohmah N, Efendi L, Arifin R, Wardoyo FA, Wilson W, Mukaromah AH, Dewi SS, Darmawati S. 2021. Antifungal activities of the rhizome extract of five member Zingiberaceae against Candida albicans and Trichophyton rubrum. Biodiversitas 22: 1509-1513. Fungal infections have now become serious health issues. One of the strategies to avoid the problems of fungal infections is by using natural product from plants that are effective against many human pathogenic fungi. The study portrayed the use of the extracts of plant rhizomes as the alternatives to fight against number of human pathogenic fungi. This research aimed to investigate the antifungal activities of crude ethanol extract of five member of the family Zingiberaceae (Curcuma longa, Alpinia galanga Zingiber officinale. var. rubrum, Zingiber officinale var. officinarum and Zingiber officinale var. amarum), which are widely used as folk medicines against Candida albicans and Trichophyton rubrum. Crude ethanol extracts of five members of Zingiberaceae were evaluated for their antifungal activities and the results were calculated based on the zones of inhibition using the diffusion method. The extract showed antifungal activity against Candida. albicans in the agar well diffusion assay (10.2-27.1 mm inhibition diameter) and against T. rubrum (27.3-44.3 mm inhibition diameter). The data have revealed that all rhizomes have the potential to be developed as antifungal agents, particularly against C. albicans and T. rubrum. Studies on the antifungal activity against yeast-like (C. albicans) and filamentous (T. rubrum) can provide new information about the benefits of members Zingiberaceae as a source of natural antifungal. Researchers can select the type of rhizome that has more potential for further extraction to obtain pure compounds that can be used as antifungals.